"SOCIAL AGRICULTURE": A PATTERN BETWEEN FARM INNOVATION, SOCIAL RESPONSIBILITY AND MULTIFUNCTIONALITY - Carmela Macrì, Maria; Angela Perito, Maria (Economics of Agriculture, 2018)
Rural context and agricultural process are assuming growing credibility as a mean to promote well being and social inclusion in the population as a whole. Fattoria solidale del Circeo" constitutes one of the many examples of social agriculture that have risen in the recent years in Italy. Differently from the general case, it is a large farm which is moving from a conventional an intensive farming system to another model, without abandoning its entrepreneurial nature. Even if it is not easy to assign a theoretic paradigm, it could be useful both in order to understand it and to give correct instruments to policy makers. So we can try to put the Fattoria Solidale del Circeos experience in a theoretic context. It seems to us that at least three different models can be applied: the wellestablished Schumpeterian model of innovation; the Corporate Social Responsibility, the Multifunctionality of agriculture.